miR-365-3p mediates BCL11A and SOX6 erythroid-specific coregulation: A new player in HbF activation - Simbula, Michela; Manchinu, Maria Francesca; Mingoia, Maura; Pala, Mauro; Asunis, Isadora; Caria, Cristian Antonio; Perseu, Lucia; Shah, Manan; Crossley, Merlin; Moi, Paolo; Ristaldi, Maria Serafina (Molecular therapy. Nucleic acids, 2023)
Hemoglobin switching is a complex biological process not yet fully elucidated. The mechanism regulating the suppression of fetal hemoglobin (HbF) expression is of particular interest because of the positive impact of HbF on the course of diseases such as β-thalassemia and sickle cell disease, hereditary hemoglobin disorders that affect the health of countless individuals worldwide. Several transcription factors have been implicated in the control of HbF, of which BCL11A has emerged as a major player in HbF silencing. SOX6 has also been implicated in silencing HbF and is critical to the silencing of the mouse embryonic hemoglobins. BCL11A and SOX6 are co-expressed and physically interact in the erythroid compartment during differentiation. In this study, we observe that BCL11A knockout leads to post-transcriptional downregulation of SOX6 through activation of microRNA (miR)-365-3p. Downregulating SOX6 by transient ectopic expression of miR-365-3p or gene editing activates embryonic and fetal β-like globin gene expression in erythroid cells. The synchronized expression of BCL11A and SOX6 is crucial for hemoglobin switching. In this study, we identified a BCL11A/miR-365-3p/SOX6 evolutionarily conserved pathway, providing insights into the regulation of the embryonic and fetal globin genes suggesting new targets for treating β-hemoglobinopathies. [Display omitted] Maria Serafina Ristaldi and colleagues describe the discovery of an evolutionarily conserved BCL11A/microRNA-365-3p/SOX6 pathway involved in the suppression of embryonic and fetal β-like globin genes. Their findings could lead to the development of new therapeutic strategies for β-thalassemia and sickle cell disease (SCD), genetic disorders that affect millions of individuals worldwide.